CORAK BUDAYA PATRIARKI DALAM PERKEMBANGAN ILMU DAN TEKNOLOGI: PERSPEKTIF EKOFEMINISME VANDANA SHIVA - Krisna Suksma Yogiswari (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2018)
This discussion aims to see the pattern of patriarchal culture taking part in the development of science and technology. This then creates a different space for women and men, especially in the development of science and technology in Asian countries. This discussion tries to see the current pattern of development of science and technology through the ecofeminism point of view of Vandana Shiva. The results of the analysis prove that the tendency of the pattern of development of science and technology today cannot be denied, many get influence from the West. That the progress of science and technology is so rapid as if it wants to match the development of the Western world, not necessarily in accordance with the character of Indonesianness and the character of Asian society